Lithium ion battery
By using core-shell structure and metal oxide coating in the positive electrode material of lithium-ion batteries, and adding fluorine-containing additives to the electrolyte, the problem of the coating peeling of lithium-ion batteries under high temperature conditions is solved, and the problem of improvement of the coating is improved High temperature storage and cycling performance of the battery.
Patent Information
- Application Number
- CN202411812798.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-07
AI Technical Summary
Under high voltage systems, the coating layer may peel off or deteriorate during long-term high-temperature charging and discharging of the positive electrode material of lithium-ion batteries, resulting in reduced battery high-temperature cycling performance and high-temperature gas production problems.
Using a positive electrode active material with a core-shell structure, the core includes Li(1+x)NiyCozM(1-y-z)O2, the coating is composed of metal oxides, and specific additives are added to the electrolyte, including fluorine atoms. , to enhance the bonding force between the cladding layer and the core material.
It effectively improves the high-temperature storage and high-temperature circulation performance of lithium-ion batteries, prevents the cladding from peeling off, reduces the problem of high-temperature gas production, and maintains good charging and discharge performance.
Smart Images

Figure BDA0005180972020000021 
Figure BDA0005180972020000022 
Figure BDA0005180972020000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium ion battery. Background Art
[0002] Under high voltage system, the catalytic activity of cobalt is enhanced. As metal ions are dissolved, the crystal structure of the positive electrode material changes, resulting in a decrease in the electronic conductivity of the material, thus affecting the charge and discharge performance of the battery. This can be improved by coating the positive electrode material, but in practical applications, coating technology still faces some challenges. During long-term high-temperature charging and discharging, the coating layer may gradually peel off or deteriorate, resulting in a decrease in the high-temperature cycle performance of the battery and high-temperature gas production problems.
[0003] Therefore, it is necessary to further optimize lithium-ion batteries to effectively improve the high-temperature storage performance and high-temperature cycle performance of the battery and ensure high charge and discharge performance. Summary of the invention
[0004] In view of the above-mentioned defects, the present invention provides a lithium ion battery having high high temperature storage performance and high temperature cycle performance, and having good charge and discharge performance.
[0005] The present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode active material, the positive electrode active material comprises a core and a coating layer arranged on at least a portion of the surface of the core;
[0006] The coating layer includes a metal oxide, and the core includes a chemical composition shown in Formula 1,
[0007] Li (1+x) Ni y Co z M (1-y-z) O2 Formula 1
[0008] In formula 1, -0.1≤x≤1, 0≤y≤1, 0≤z≤1, and M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr;
[0009] The electrolyte includes an additive, and the additive includes a structure shown in Formula 2,
[0010]
[0011] In formula 2, R1, R2, R3, R4, R5, and R6 are independently selected from halogen atoms, substituted or unsubstituted C1-C10 alkyl groups, substituted or unsubstituted C2-C10 alkenyl groups, and substituted or unsubstituted C2-C10 alkynyl groups. The substituents include at least one of halogen atoms, hydroxyl groups, carboxyl groups, cyano groups, amino groups, ester groups, alkenyl groups, and alkynyl groups. n is 0-2.
[0012] Furthermore, the lithium-ion battery satisfies Formula 3,
[0013] 0.1≤A / B≤390 Formula 3
[0014] In Formula 3, A is the mass percentage of the compound having the structure of Formula 2 in the electrolyte, in units of wt%; B is the thickness of the coating layer, in units of nm;
[0015] Preferably, the mass percentage A of the additive in the electrolyte is 0.5wt%-20wt%;
[0016] Preferably, the coating layer has a thickness B of 0.05 nm to 5 nm.
[0017] Furthermore, the structure shown in Formula 2 includes at least 4 fluorine atoms;
[0018] Preferably, the additive includes at least one of the structures shown in Formula 2-1, Formula 2-2, Formula 2-3, Formula 2-4, and Formula 2-5.
[0019]
[0020] Further, the metal oxide includes at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, niobium oxide, and molybdenum oxide;
[0021] And / or, the coating layer further comprises a carbon material and / or a conductive polymer;
[0022] Preferably, the carbon material includes at least one of hard carbon, soft carbon, graphene, carbon nanotubes, porous activated carbon, and carbon black;
[0023] Preferably, the conductive polymer includes at least one of polyacrylonitrile, polypyrrole, polyacetylene and polythiophene.
[0024] Further, M includes Al and / or Mg;
[0025] Preferably, the mass percentage of Al in the positive electrode active material is 2000ppm-12000ppm;
[0026] Preferably, the mass percentage of Mg in the positive electrode active material is 100 ppm-4000 ppm.
[0027] Furthermore, the electrolyte further comprises nitrile compounds; the nitrile compounds comprise dinitrile compounds and / or trinitrile compounds;
[0028] Preferably, the dinitrile compounds include succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4 ,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol 2-cyanoethyl alcohol ether, triethylene glycol bis(2-cyanoethyl) ether, tetraethylene glycol bis(2-cyanoethyl) ether, 3,6,9,12,15,18-hexaoxaicosanoic acid dinitrile, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol bis(4-cyanobutyl) ethers, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene and 1,6-dicyano;
[0029] Preferably, the trinitrile compound includes but is not limited to one or more of 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, tris(cyanoethyl)phosphate, 1,2,6-tris(cyanoethoxy)hexane and 1,2,5-tris(cyanoethoxy)pentane.
[0030] Furthermore, the lithium-ion battery satisfies Formula 4,
[0031] P / (C+A)≤10 Formula 4
[0032] In Formula 4, P is the mass percentage of the cobalt element in the positive electrode active material, in wt%; C is the mass percentage of the nitrile compound in the electrolyte, in wt%; A is the mass percentage of the compound having the structure of Formula 2 in the electrolyte, in wt%.
[0033] Furthermore, the mass percentage content P of the cobalt element in the positive electrode active material is 54.8wt%-63.1wt%;
[0034] And / or, the mass percentage C of the nitrile compound in the electrolyte is 0.5wt%-8wt%.
[0035] Furthermore, the porosity D of the positive electrode sheet is 10%-30%.
[0036] Furthermore, the lithium-ion battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material; the mass percentage E of silicon in the negative electrode active material is 1wt%-30wt%;
[0037] And / or, the thickness of the negative electrode active material layer is 50 μm-150 μm.
[0038] The lithium-ion battery in the present invention includes a positive electrode active material with a core-shell structure and a special additive, wherein the core-shell structure specifically includes a core and a coating layer arranged on at least a portion of the surface of the core, the bulk phase of the core portion is doped with M elements, and the coating layer includes a metal oxide, and the additive includes a structure shown in Formula 2. At this time, the additive can cooperate with the positive electrode active material to effectively improve the high-temperature storage performance and high-temperature cycle performance of the battery, and ensure good charge and discharge performance. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The present invention provides a lithium ion battery, which includes a positive electrode sheet and an electrolyte; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a core and a coating layer arranged on at least a part of the surface of the core;
[0041] The coating layer includes a metal oxide, and the core includes a chemical composition shown in Formula 1,
[0042] Li(1+x) Ni y Co z M (1-y-z) O2 Formula 1
[0043] In formula 1, -0.1≤x≤1, 0≤y≤1, 0≤z≤1, and M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr;
[0044] The electrolyte includes an additive, and the additive includes a structure shown in Formula 2,
[0045]
[0046] In formula 2, R1, R2, R3, R4, R5, and R6 are independently selected from halogen atoms, substituted or unsubstituted C1-C10 alkyl groups, substituted or unsubstituted C2-C10 alkenyl groups, and substituted or unsubstituted C2-C10 alkynyl groups. The substituents include at least one of halogen atoms, hydroxyl groups, carboxyl groups, cyano groups, amino groups, ester groups, alkenyl groups, and alkynyl groups. n is 0-2.
[0047] The "C1-C10 alkyl group" in the present invention refers to a saturated straight-chain alkane or saturated branched alkane containing 1 to 10 carbon atoms, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl.
[0048] The "C2-C10 alkenyl" in the present invention refers to a straight-chain alkenyl or branched alkenyl having 2 to 10 carbon atoms and containing one or more double bonds, for example, ethenyl, 1-propenyl, 2-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1,3-butadienyl, and 3-methyl-2-butenyl.
[0049] The "C2-C10 alkynyl group" in the present invention refers to a straight-chain or branched alkynyl group having 2 to 10 carbon atoms and containing one or more triple bonds, for example, ethynyl, propynyl, butynyl.
[0050] The "halogen atom" in the present invention refers to fluorine, chlorine, bromine or iodine.
[0051] In the present invention, when n=0, the structure shown in Formula 2 is a five-membered ring, when n=1, the structure shown in Formula 2 is a six-membered ring, and when n=2, the structure shown in Formula 2 is a seven-membered ring.
[0052] The compound shown in Formula 2 in the present invention is an ionic compound, including an anion and a cation. The anion has a structure shown in Formula 2, and the cation can be a sodium ion or a lithium ion.
[0053] The present invention is not limited to the metal element in the metal oxide, for example, it can be at least one of Mg, Al, Ti, Zn, Ga, Ba, Fe, Cr, and Mn.
[0054] The lithium ion battery of the present invention comprises a positive electrode active material having a core-shell structure and an additive of the structure of formula 2. The additive of formula 2 can penetrate into the interface between the core of the positive electrode material and the coating layer, and react with the metal ions on the surface of the core material to effectively inhibit the dissolution of transition metal ions, thereby reducing the side reactions caused by the dissolution of transition metal ions; and a thin and dense CEI film is generated at the interface between the core of the positive electrode active material and the coating layer. The CEI film enhances the bonding effect between the coating layer and the core material, and can inhibit the peeling or deterioration of the coating layer during long-term high-temperature charging and discharging without affecting the charging and discharging of the battery, prevent the problem of high-temperature gas generation, and improve the high-temperature storage performance and high-temperature cycle performance of the battery. Therefore, the lithium ion battery in the present application has high high-temperature storage performance and high-temperature cycle performance, as well as good charging and discharging performance.
[0055] In addition, since the positive electrode active material in the present application has a metal oxide coating layer, the core part can be effectively coated to avoid direct contact between the electrolyte and the core material, thereby avoiding oxidative decomposition of the electrolyte, further improving the high temperature storage performance and high temperature cycle performance of the battery.
[0056] In one specific embodiment, the lithium-ion battery satisfies Formula 3,
[0057] 0.1≤A / B≤390 Formula 3
[0058] In Formula 3, A is the mass percentage of the compound having the structure of Formula 2 in the electrolyte, in units of wt%; B is the thickness of the coating layer, in units of nm.
[0059] For example, when the mass percentage of the compound having the structure of Formula 2 in the electrolyte is 20wt% and the thickness of the coating layer is 5nm, A / B is 4.
[0060] When the lithium-ion battery satisfies Formula 3, it can not only prevent the coating layer from being too thick to affect the penetration of the additive in Formula 2, but also prevent the coating layer from being too thin to isolate the electrolyte from the core material; at the same time, the content of the additive is relatively appropriate, which can not only fully complex with the metal ions on the surface of the core, but also ensure the formation of the CEI film and enhance the bonding force between the coating layer and the core material. Therefore, when the lithium-ion battery satisfies Formula 3, the high-temperature storage performance and high-temperature cycle performance of the lithium-ion battery can be further improved, and it has a higher charge and discharge performance.
[0061] Preferably, the mass percentage A of the additive in the electrolyte is 0.5wt%-20wt%. For example, the mass percentage A is 0.5wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%. Within this range, the complexation between the compound having the structure of Formula 2 and the transition metal ions in the positive electrode active material can be further enhanced, the dissolution of the transition metal ions can be effectively inhibited, and the oxidation resistance of the electrolyte can be improved, thereby improving the high temperature cycle performance and high temperature storage performance of the lithium ion battery.
[0062] Preferably, the thickness B of the coating layer is 0.05nm-5nm; preferably 1nm-2nm. For example, the thickness B of the coating layer is 0.05nm, 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm. Within this range, the coating layer can not only cover the surface of the core material to a large extent, but also reduce the side reaction between the electrolyte and the positive electrode active material, ensure the charge and discharge performance of the battery, and improve the high temperature storage performance and high temperature cycle performance of the battery.
[0063] In a specific embodiment, the structure shown in Formula 2 includes at least 4 fluorine atoms. For example, the structure shown in Formula 2 includes 4, 5, 6, 7, 8, 9, 10, 11, and 12 fluorine atoms. At this time, the overall oxidation resistance of the molecule including the structure of Formula 2 can be further improved, so that the electrolyte including the structure exhibits higher oxidation resistance at high voltage.
[0064] Preferably, the additive includes at least one of the structures shown in Formula 2-1, Formula 2-2, Formula 2-3, Formula 2-4, and Formula 2-5.
[0065]
[0066] When the additive includes at least two of the compounds of formula 2-1, 2-2, 2-3, 2-4, and 2-5, the present invention does not specifically limit the ratio of each compound.
[0067] In a specific embodiment, the metal oxide includes at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, niobium oxide, and molybdenum oxide. The aforementioned metal oxides have high thermal stability, can maintain structural stability in a high temperature environment, and improve the high temperature storage performance and high temperature cycle performance of the battery.
[0068] In a specific embodiment, the coating layer also includes carbon material and / or conductive polymer; preferably, the carbon material includes at least one of hard carbon, soft carbon, graphene, carbon nanotubes, porous activated carbon, and carbon black; preferably, the conductive polymer includes at least one of polyacrylonitrile, polypyrrole, polyacetylene, and polythiophene.
[0069] When the coating layer also includes carbon material and / or conductive polymer, the electronic conductivity of the electrode material can be significantly improved, further improving the charge and discharge performance of the battery.
[0070] When the coating layer includes multiple specific substances among the aforementioned substances at the same time, the present invention does not specifically limit the ratio between the various substances.
[0071] In a specific embodiment, M includes Al and / or Mg; preferably, the mass percentage of Al in the positive electrode active material is 2000ppm-12000ppm, and preferably, the mass percentage of Mg in the positive electrode active material is 100ppm-4000ppm. When M includes Al and / or Mg, and further, the mass percentage of Al and Mg in the positive electrode active material is within the aforementioned range, a high structural stability can be ensured, the dissolution of transition metal ions can be suppressed, and the collapse of the positive electrode active material structure can be prevented.
[0072] Illustratively, the mass percentage of Al in the positive electrode active material is 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, 10000 ppm, 11000 ppm or 12000 ppm.
[0073] Illustratively, the mass percentage of Mg in the positive electrode active material is 100 ppm, 200 ppm, 300 ppm, 500 ppm, 700 ppm, 900 ppm, 1100 ppm, 1500 ppm, 2000 ppm, 3000 ppm, or 4000 ppm.
[0074] When M is Al and Mg at the same time, the present invention does not specifically limit the ratio of Al to Mg.
[0075] In a specific embodiment, the electrolyte further comprises a nitrile compound; the nitrile compound comprises a dinitrile compound and / or a trinitrile compound;
[0076] Preferably, the dinitrile compounds include succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4- Tetramethylglutaronitrile, 1,4-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2 -cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 3,6,9,12,15,18-hexaoxaicosanoic acid dinitrile, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl) ether, 1,4 - at least one of dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene and 1,6-dicyano;
[0077] Preferably, the trinitrile compound includes at least one of 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, tris(cyanoethyl)phosphate, 1,2,6-tris(cyanoethoxy)hexane and 1,2,5-tris(cyanoethoxy)pentane.
[0078] When the electrolyte includes the aforementioned nitrile compound, the additive including the structure of Formula 2 can undergo ion exchange or coordination with the nitrogen atoms in the nitrile compound to form a stable ion pair or complex, thereby improving the complexation with the transition metal ions in the positive electrode active material, thereby further improving the high temperature cycle performance of the battery.
[0079] When the aforementioned nitrile compound is a mixture of the aforementioned multiple specific compounds, the present invention does not specifically limit the ratio between the various specific compounds.
[0080] The present invention does not specifically limit the specific source of the nitrile compound, and a commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0081] In one specific embodiment, the lithium ion battery satisfies Formula 4,
[0082] P / (C+A)≤10 Formula 4
[0083] In Formula 4, P is the mass percentage of cobalt element in the positive electrode active material, in units of wt%; C is the mass percentage of nitrile compound in the electrolyte, in units of wt%; A is the mass percentage of the compound including the structure of Formula 2 in the electrolyte, in units of wt%;
[0084] Illustratively, when the mass percentage P of the cobalt element in the positive electrode active material is 60wt%, the mass percentage A of the compound having the structure of Formula 2 in the electrolyte is 20wt%, and the mass percentage C of the nitrile compound in the electrolyte is 5wt%, P / (C+A)=60 / (20+5)=2.4.
[0085] The cobalt content in the positive electrode active material determines the capacity of the battery and can effectively improve the capacity of the battery. However, when the cobalt content is too high, the additive of formula 2 and the nitrile compound are not sufficient to protect the positive electrode active material and cannot be well complexed with the cobalt ions in the material, causing the volume expansion of the positive electrode active material and resulting in a decrease in capacity. When the mass content of the additive of formula 2 and the nitrile compound in the electrolyte is too high, it will lead to increased polarization, increased internal resistance, and decreased cycle capacity retention rate.
[0086] In a specific embodiment, the mass percentage content P of the cobalt element in the positive electrode active material is 54.8wt%-63.1wt%. Within this range, the positive electrode active material can better cooperate with the compound including the structure of Formula 2 and the nitrile additive to further improve the high temperature cycle performance and capacity of the battery.
[0087] Illustratively, the mass percentage is 54.8wt%, 55.0wt%, 56.0wt%, 57.0wt%, 58.0wt%, 59.0wt%, 60.0wt%, 61.0wt%, 62.0wt% or 63.1wt%.
[0088] In a specific embodiment, the mass percentage C of the nitrile compound in the electrolyte is 0.5wt%-8wt%. Within this range, the nitrile compound can better interact with the compound represented by Formula 2 to generate a stable ion pair or complex, thereby further enhancing the complexation of the complex or ion pair with the metal ions in the positive electrode active material, so that the battery has higher high temperature cycle performance and capacity.
[0089] Exemplarily, the mass percentage is 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt% or 8 wt%.
[0090] In a specific embodiment, the porosity D of the positive electrode sheet is 10% - 30%.
[0091] For a high-voltage battery system, the compaction density of the positive electrode sheet is often relatively large. However, too high a compaction density will result in a relatively small porosity of the positive electrode sheet, which will affect the insertion and extraction of lithium ions in the positive electrode, and the compound including the structure of Formula 2 in the electrolyte will reduce the lithium ion transport rate. When the porosity of the positive electrode sheet is within the aforementioned range, the contact sites between the electrode sheet and the electrolyte can be increased, and the electrolyte will be more easily infiltrated into the interior of the sheet, which helps the efficient and rapid transport of lithium ions, further improving the rate performance of the battery, and at the same time, the loss of energy density can be reduced.
[0092] Exemplarily, the porosity C is 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%.
[0093] In a specific embodiment, the lithium ion battery further includes a negative electrode sheet, the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material; the mass percentage E of silicon in the negative electrode active material is 1 wt% - 30 wt%.
[0094] Although the silicon-containing negative electrode active material (silicon-based negative electrode active material) has a relatively high energy density, its conductivity is poor. However, the fluorine atom in the compound including the structure of Formula 2 in the electrolyte has strong electron-withdrawing properties, which can effectively improve the conductivity of the negative electrode sheet, and the ring structure therein can effectively weaken the coordination effect between the cation and anion in the lithium salt, making the lithium ions more active, comprehensively improving the kinetic performance of the electrolyte. Therefore, when the mass percentage E of silicon in the negative electrode active material is within the above range, the silicon-based negative electrode active material and the compound including the structure of Formula 2 in the electrolyte can cooperate with each other to effectively improve the low-temperature discharge performance and energy density of the lithium ion battery.
[0095] Exemplarily, the mass percentage is 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30%.
[0096] The silicon-based negative electrode active material in the present invention is preferably at least one of nano-silicon (Si), silicon-oxygen negative electrode material (SiO x , 0 < x < 2) and silicon-carbon negative electrode material.
[0097] In a specific embodiment, the average sphericity of the negative electrode active material is 0.5 - 1.0.
[0098] The "average sphericity" in the present invention is obtained by testing including the following steps: performing SEM testing on the negative electrode active material to obtain a SEM image with a magnification of 2500 times; analyzing each particle in the SEM image through image processing software (such as Image Pro Plus) to obtain the perimeter and area of each particle, and calculating the perimeter equivalent radius R1 and area equivalent radius R2 of each particle respectively, then the sphericity S of each particle = R2 / R1, and then taking the average value of the sphericity of each particle to obtain the average sphericity of the composite material.
[0099] Within this range, the negative electrode active materials can be better accumulated in the negative electrode active material layer to form a denser negative electrode active material layer, which is beneficial to improving the energy density of the battery; at the same time, since the silicon-containing negative electrode active materials will undergo significant volume expansion and contraction during the charge and discharge process, the negative electrode active materials with good sphericity can better withstand this volume change due to their uniform stress distribution, reduce material breakage and shedding, and improve the battery's cycle performance.
[0100] In a specific embodiment, the thickness of the negative electrode active material layer is 50 μm-150 μm. Within this range, not only a higher energy density can be ensured, but also the lithium-ion battery can have a higher cycle performance.
[0101] The thickness of the negative electrode active material layer in the present invention refers to the thickness of the negative electrode active coating layer disposed on either side of the negative electrode current collector.
[0102] Illustratively, the thickness of the negative electrode active material layer is 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, or 150 μm.
[0103] Preferably, the thickness of the negative electrode current collector in the negative electrode sheet is 2 μm-10 μm, which is beneficial to further improve the energy density of the battery.
[0104] In a specific embodiment, the negative electrode sheet also includes a carbon-based negative electrode active material; the carbon-based negative electrode active material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon, and soft carbon.
[0105] In a specific embodiment, the electrolyte further includes an organic solvent, a lithium salt and a functional additive.
[0106] The organic solvent includes carbonates and / or carboxylates; wherein the carbonate includes at least one of fluorinated or unsubstituted ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; the carboxylates include at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate, and ethyl butyrate.
[0107] The lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonylimide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, and lithium bis(trifluoromethylsulfonyl)imide.
[0108] The functional additives include at least one of vinylene carbonate, vinyl carbonate, vinyl sulfate, suberonitrile, suberonitrile, glycerol trinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3-propane sultone, propenyl-1,3-sultone, and 1,3-propane sultone.
[0109] Hereinafter, a lithium-ion battery including the electrolyte of the present invention will be described in detail through specific embodiments.
[0110] Example 1
[0111] This embodiment provides a lithium ion battery, and the preparation method thereof comprises the following steps:
[0112] 1) Preparation of positive electrode
[0113] The positive electrode active material (the core is LiCoO2 doped with Al, the coating is alumina, the thickness of the coating is 2.5nm, the mass percentage of Al is 3500ppm, the mass percentage of cobalt is 56.8wt%), the conductive agent carbon nanotubes, polyvinylidene fluoride (PVDF), according to the mass ratio of 97.6:1.4:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum stirrer to obtain a positive electrode active slurry; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain a slurry with a porosity of 20% and a surface density of 16mg / cm 2 , compacted density is 4.15g / cm 3 The positive electrode;
[0114] 2) Negative electrode preparation
[0115] The negative electrode active material (90wt% artificial graphite and 10wt% silicon carbon material, with an average sphericity of 0.75), conductive agent Super-P, carboxymethyl cellulose lithium, and binder polyacrylic acid (PAA) were mixed in a mass ratio of 97:0.4:0.1:2.5, and deionized water was added to obtain a negative electrode active slurry under the action of a vacuum mixer; the negative electrode active slurry was evenly coated on both surfaces of the copper foil; the coated copper foil was dried at room temperature, and then dried, cold pressed, and cut to obtain a copper foil with a thickness of 90μm and a surface density of 9.5mg / cm 2 , compacted density is 1.75g / cm 3 The negative electrode.
[0116] 3) Isolation film
[0117] A polyethylene membrane with a thickness of 8 μm and a porosity of 40% was selected.
[0118] 4) Preparation of electrolyte
[0119] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), propyl propionate (PP), and fluoroethylene carbonate (FEC) are uniformly mixed in a mass ratio of 1:1:2:5.7:1.7 to obtain an organic solvent; then, 14wt% of fully dried lithium salt lithium hexafluorophosphate (LiPF6), 2wt% of adiponitrile, and 1wt% of succinonitrile based on the total mass of the electrolyte are quickly added thereto, and after dissolution, 3wt% of a compound having a structure shown in Formula 2-1 (the cation is Li + ), 3 wt % of functional additive 1,3-propane sultone, after being stirred evenly, and after being tested for water content and free acid and being qualified, an electrolyte is obtained.
[0120] 5) Preparation of lithium-ion batteries
[0121] The positive electrode sheet prepared in step 1), the negative electrode sheet prepared in step 2), and the separator prepared in step 3) are stacked in the order of positive electrode sheet, separator, and negative electrode sheet, and then wound to obtain a battery cell. The battery cell is placed in an outer packaging aluminum foil, and the electrolyte prepared in step 4) is injected into the outer packaging. After vacuum packaging, standing, formation, shaping, sorting and other processes, the lithium-ion battery of this embodiment is obtained.
[0122] Example 2
[0123] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound having the structure shown in Formula 2-1 is replaced by a compound having the structure shown in Formula 2-3, and the mass percentage of the compound having the structure shown in Formula 2-3 in the electrolyte is adjusted to 5wt%.
[0124] Example 3
[0125] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound having the structure shown in Formula 2-1 is replaced by a compound having the structure shown in Formula 2-4, and the mass percentage of the compound having the structure shown in Formula 2-3 in the electrolyte is adjusted to 10wt%.
[0126] Example 4
[0127] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the compound having the structure shown in Formula 2-1 is replaced by a compound having the structure shown in Formula 2-5, and the mass percentage of the compound having the structure shown in Formula 2-3 in the electrolyte is adjusted to 20wt%.
[0128] Example 5
[0129] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the core is Mg-doped LiCoO2, and the mass percentage content remains unchanged.
[0130] Example 6
[0131] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the core is Zn-doped LiCoO2, and the mass percentage content remains unchanged.
[0132] Example 7
[0133] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the coating layer in the positive electrode active material is zirconium oxide ZrO2.
[0134] Example 8
[0135] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the coating layer in the positive electrode active material is magnesium oxide MgO.
[0136] Example 9
[0137] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the coating layer in the positive electrode active material is titanium oxide TiO2.
[0138] Example 10
[0139] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the coating layer in the positive electrode active material also includes graphene, the mass ratio of aluminum oxide to graphene is 1:1, and the thickness of the coating layer remains unchanged.
[0140] Embodiment 11
[0141] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Example 1, except that in step 1), the coating layer in the positive electrode active material also includes polyacrylonitrile (number average molecular weight 1000), the mass ratio of aluminum oxide to polyacrylonitrile is 1:1, and the thickness of the coating layer remains unchanged.
[0142] Example 12
[0143] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass percentage content of Al in the positive electrode active material is 2000 ppm.
[0144] Example 13
[0145] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass percentage content of Al in the positive electrode active material is 5000 ppm, and the mass percentage content of Mg in the positive electrode active material is 1000 ppm.
[0146] Embodiment 14
[0147] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the thickness of the coating layer in the positive electrode active material is 0.05 nm.
[0148] Embodiment 15
[0149] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the thickness of the coating layer in the positive electrode active material is 5 nm.
[0150] Example 16
[0151] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass percentage of the compound having the structure shown in Formula 2-1 in the electrolyte is adjusted to 0.5wt%.
[0152] Embodiment 17
[0153] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass percentage of the compound having the structure shown in Formula 2-1 in the electrolyte is adjusted to 20wt%.
[0154] Embodiment 18
[0155] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 14, except that in step 4), the mass percentage of the compound having the structure shown in Formula 2-1 in the electrolyte is adjusted to 1.5wt%.
[0156] Embodiment 19
[0157] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass percentage of the compound having the structure shown in Formula 2-1 in the electrolyte is adjusted to 0.3wt%.
[0158] Embodiment 20
[0159] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the coating thickness of the positive electrode active layer is 7 nm.
[0160] Embodiment 21
[0161] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass percentage content of Al in the positive electrode active material is 1800 ppm.
[0162] Embodiment 22
[0163] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 22, except that in step 1), the porosity of the positive electrode sheet is 10%.
[0164] Embodiment 23
[0165] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 22, except that in step 1), the porosity of the positive electrode sheet is 30%.
[0166] Embodiment 24
[0167] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 22, except that in step 1), the porosity of the positive electrode sheet is 7%.
[0168] Embodiment 25
[0169] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 22, except that in step 2), the mass percentage of the silicon-carbon material in the negative electrode active material is 5wt%.
[0170] Embodiment 26
[0171] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 22, except that in step 2), the mass percentage of the silicon-carbon material in the negative electrode active material is 30wt%.
[0172] Embodiment 27
[0173] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 22, except that in step 2), the mass percentage of the silicon-carbon material in the negative electrode active material is 35wt%.
[0174] Embodiment 28
[0175] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 22, except that in step 2), the thickness of the negative electrode sheet is adjusted to 70 μm by reducing the thickness of the negative electrode active layer.
[0176] Embodiment 29
[0177] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 22, except that in step 2), the thickness of the negative electrode sheet is adjusted to 120 μm by increasing the thickness of the negative electrode active layer.
[0178] Embodiment 30
[0179] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 22, except that in step 2), the thickness of the negative electrode sheet is adjusted to 130 μm by increasing the thickness of the negative electrode active layer.
[0180] Embodiment 31
[0181] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 22, except that in step 2), the negative electrode active material only includes graphite.
[0182] Embodiment 32
[0183] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass percentage of the Co element in the positive electrode active material is 54.8wt%;
[0184] In step 4), the mass content of adiponitrile in the electrolyte is 4 wt %, and the mass content of succinonitrile is 2 wt %.
[0185] Embodiment 33
[0186] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass percentage of the Co element in the positive electrode active material is 63.1 wt %.
[0187] Embodiment 34
[0188] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the electrolyte further includes 1,3,6-hexanetrinitrile, and the mass percentage of 1,3,6-hexanetrinitrile in the electrolyte is 0.5wt%.
[0189] Embodiment 35
[0190] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 37, except that in step 4), the mass percentage of 1,3,6-hexanetricarbonitrile in the electrolyte is 5wt%.
[0191] Embodiment 36
[0192] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass percentage of the Co element in the positive electrode active material is 50 wt %.
[0193] Embodiment 37
[0194] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of adiponitrile in the electrolyte is 6 wt %, and the mass content of succinonitrile is 3 wt %.
[0195] Embodiment 38
[0196] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass content of adiponitrile in the electrolyte is 0.3 wt %, and the mass content of succinonitrile is 0.3 wt %.
[0197] Comparative Example 1
[0198] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that in step 1), the positive electrode active material does not contain a coating layer.
[0199] Comparative Example 2
[0200] The preparation method of the lithium-ion battery in this comparative example is basically the same as that in Example 1, except that in step 4), the electrolyte does not include a compound having a structure shown in Formula 2-1.
[0201] Test example
[0202] 1. The lithium ion batteries prepared in the above-mentioned Examples 1 to 31 and Comparative Examples 1 to 2 were subjected to the following tests:
[0203] 1) High temperature storage performance
[0204] At 25℃±5℃, test the battery state voltage, internal resistance and thickness d0, and let it stand for 10 minutes; discharge at 0.2C to the lower limit voltage of 3.0V, and let it stand for 10 minutes; then charge at 0.7C to the upper limit voltage of 4.55V, cut off at 0.05C, and let it stand for 10 minutes; then discharge at 0.2C to the lower limit voltage to obtain the initial discharge capacity; after standing for 10 minutes, charge at 0.7C to the upper limit voltage, cut off at 0.05C; let it stand for 10 minutes; store the battery at 85℃±2℃ for 6 hours; take out after storage, and immediately test the battery thickness d1, then the battery thickness expansion rate (%) = (d1-d0) / d0×100%.
[0205] 2) High temperature cycle performance
[0206] The sample was tested at 45°C and allowed to stand for 10 minutes; discharged at 1C to a lower voltage of 3.0V and allowed to stand for 10 minutes; charged at 1C at 45°C to an upper voltage of 4.55V, with a cutoff current of 0.025C, and allowed to stand for 10 minutes; discharged at a rate of 1.2C to a cutoff voltage of 3.0V in a 45°C constant temperature box environment and allowed to stand for 10 minutes; the initial discharge capacity was recorded; the sample was cycled 600 times according to the above-mentioned charge and discharge mechanism, and the discharge capacity after 600 cycles of high-temperature cycling was recorded. The high-temperature cycle capacity retention rate is the ratio of the discharge capacity after the cycle to the initial discharge capacity.
[0207] 3) Room temperature rate performance
[0208] Test the voltage, internal resistance and thickness of the lithium-ion battery sample at 25℃, and let it stand for 10 minutes; charge at 1C to an upper limit voltage of 4.55V, a cut-off current of 0.025C, discharge at 1C to a lower limit voltage of 3.0V, measure the initial discharge capacity, and let it stand for 10 minutes; charge at 1C to an upper limit voltage of 4.55V, a cut-off current of 0.025C in a constant temperature room, and let it stand for 10 minutes; discharge at a rate of 3C to a cut-off voltage of 3.0V in a constant temperature box environment, and let it stand for 10 minutes; record the discharge capacity, and the room temperature rate discharge capacity retention rate is the ratio of the discharge capacity to the initial discharge capacity.
[0209] 4) Low-temperature discharge performance The lithium-ion battery was placed at 25℃±5℃ for 10 min; discharged at 0.2C to a lower voltage of 3.0V, and allowed to stand for 10 min; then charged at 0.7C to an upper voltage of 4.55V, cut off at 0.05C, and allowed to stand for 10 min; then discharged at 0.2C to a lower voltage of 3.0V to obtain the initial capacity, and allowed to stand for 10 min; then charged at 0.7C to an upper voltage of 4.55V, cut off at 0.05C, and allowed to stand for 10 min; the battery was stored at 0℃±2℃ for 2 h; taken out after storage, discharged at 0.2C to a lower voltage of 3.0V, and the discharge capacity was recorded. The capacity retention rate at low temperature is the ratio of the discharge capacity at low temperature to the initial capacity.
[0210] 5) Energy density
[0211] The lithium-ion battery is charged at a constant current of 0.2C to 4.55V, and then charged at a constant voltage to a cut-off current of 0.05C to fully charge the lithium-ion battery; next, it is discharged at a constant current of 0.2C until the voltage of the lithium-ion battery drops to 3.0V, and the total discharge capacity during the discharge process is recorded as Q, and the actual volume V of the lithium-ion battery is calculated, and the volume energy density is the ratio of Q to V.
[0212] The basic parameters are shown in Table 1 and the test results are shown in Table 2.
[0213] Table 1
[0214]
[0215]
[0216] Table 2
[0217]
[0218]
[0219] From Table 1 and Table 2, we can see that:
[0220] Compared with Comparative Examples 1 and 2, the lithium ion batteries in Examples 1 to 31 have higher high temperature storage performance, high temperature cycle performance, room temperature rate performance and low temperature discharge performance; among them, the battery in Example 4 has the best comprehensive performance, with a high temperature storage expansion rate as low as 4.9%, a high temperature cycle capacity retention rate as high as 93.9%, and a room temperature rate performance of up to 95.8%. Correspondingly, the low temperature discharge performance is 74.25%, and the energy density is 880Wh / kg. It can be seen that the lithium ion battery in the present invention has higher high temperature storage performance and high temperature cycle performance, and has better charge and discharge performance.
[0221] 2. The high temperature cycle capacity retention rate and capacity of the lithium ion batteries in the above-mentioned Examples 1 and 32 to 38 were tested.
[0222] 1) High temperature cycle capacity retention rate
[0223] It is consistent with the test method of the above-mentioned high temperature cycle performance.
[0224] 2) Capacity
[0225] Discharge the lithium-ion battery at 0.2C to a lower voltage of 3.0V. After standing for 10 minutes, charge it at 1C to an upper voltage of 4.55V with a cut-off current of 0.05C. At this time, the battery is fully charged. Discharge the battery at 0.2C to a lower voltage of 3.0V. The capacity released at this time is the battery capacity.
[0226] The test results are shown in Table 3.
[0227] Table 3
[0228]
[0229] From Table 3, we can see that:
[0230] By controlling the mass content C of nitrile compounds in the electrolyte and the mass content P of Co in the positive electrode active material, and making the two and the mass content A of the compound including the structure of Formula 2 in the electrolyte satisfy a specific relationship, that is, P / (C+A)≤10, the high temperature cycle capacity retention rate of the battery can be effectively improved, and the battery capacity can be improved.
[0231] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material comprises a core and a coating layer disposed on at least a portion of the surface of the core; The coating layer includes a metal oxide, and the core includes a chemical composition shown in Formula 1, Li (1+x) Ni y Co z M (1-y-z) O2 type 1 In formula 1, -0.1≤x≤1, 0≤y≤1, 0≤z≤1, and M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr; The electrolyte includes an additive, and the additive includes a structure shown in Formula 2, In formula 2, R1, R2, R3, R4, R5, and R6 are independently selected from halogen atoms, substituted or unsubstituted C1-C10 alkyl groups, substituted or unsubstituted C2-C10 alkenyl groups, and substituted or unsubstituted C2-C10 alkynyl groups. The substituents include at least one of halogen atoms, hydroxyl groups, carboxyl groups, cyano groups, amino groups, ester groups, alkenyl groups, and alkynyl groups. n is 0-2.
2. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery satisfies Formula 3, 0.1≤A / B≤390 Formula 3 In Formula 3, A is the mass percentage of the compound having the structure of Formula 2 in the electrolyte, in units of wt%; B is the thickness of the coating layer, in units of nm; Preferably, the mass percentage A of the additive in the electrolyte is 0.5wt%-20wt%; Preferably, the coating layer has a thickness B of 0.05 nm to 5 nm.
3. The lithium ion battery according to claim 1 or 2, characterized in that: The structure shown in Formula 2 includes at least 4 fluorine atoms; Preferably, the additive includes at least one of the structures shown in Formula 2-1, Formula 2-2, Formula 2-3, Formula 2-4, and Formula 2-5.
4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The metal oxide includes at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, niobium oxide, and molybdenum oxide; And / or, the coating layer further comprises a carbon material and / or a conductive polymer; Preferably, the carbon material includes at least one of hard carbon, soft carbon, graphene, carbon nanotubes, porous activated carbon, and carbon black; Preferably, the conductive polymer includes at least one of polyacrylonitrile, polypyrrole, polyacetylene and polythiophene.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: M includes Al and / or Mg; Preferably, the mass percentage of Al in the positive electrode active material is 2000ppm-12000ppm; Preferably, the mass percentage of Mg in the positive electrode active material is 100 ppm-4000 ppm.
6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The electrolyte also includes nitrile compounds; the nitrile compounds include dinitrile compounds and / or trinitrile compounds; Preferably, the dinitrile compounds include succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4 ,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol 2-cyanoethyl alcohol ether, triethylene glycol bis(2-cyanoethyl) ether, tetraethylene glycol bis(2-cyanoethyl) ether, 3,6,9,12,15,18-hexaoxaicosanoic acid dinitrile, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol bis(4-cyanobutyl) ethers, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene and 1,6-dicyano; Preferably, the trinitrile compound includes but is not limited to one or more of 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, tris(cyanoethyl)phosphate, 1,2,6-tris(cyanoethoxy)hexane and 1,2,5-tris(cyanoethoxy)pentane.
7. The lithium-ion battery according to claim 6, characterized in that: The lithium-ion battery satisfies Formula 4, P / (C+A)≤10 Formula 4 In Formula 4, P is the mass percentage of the cobalt element in the positive electrode active material, in wt%; C is the mass percentage of the nitrile compound in the electrolyte, in wt%; A is the mass percentage of the compound having the structure of Formula 2 in the electrolyte, in wt%.
8. The lithium-ion battery according to claim 7, characterized in that: The mass percentage content P of the cobalt element in the positive electrode active material is 54.8wt%-63.1wt%; And / or, the mass percentage C of the nitrile compound in the electrolyte is 0.5wt%-8wt%.
9. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The porosity D of the positive electrode sheet is 10%-30%.
10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The lithium-ion battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material; the mass percentage E of silicon in the negative electrode active material is 1wt%-30wt%; And / or, the thickness of the negative electrode active material layer is 50 μm-150 μm.
Citation Information
Patent Citations
Anode active material for lithium secondary battery, method for fabricating same, and lithium secondary battery using same
CN104904043A
Lithium ion battery and application thereof
CN113299971A
Lithium ion battery and application thereof
CN113299973A
Fluorine-containing cyclic sulfonide salt, method for preparing same, nonaqueous electrolyte solution
CN117121258A
Positive electrode active material and preparation method therefor, positive electrode sheet, battery and electric device
WO2024169379A1